AGREEMENTS KEPT ARE WARS AVOIDED - Sztuka, Maria; Półtorak, Magdalena (No Limits, 2022)
Vulnerable persons are not only women, children, and people with disabilities. This group also includes the elderly, pregnant people, single parents, victims of human trafficking, severely ill people, those suffering from mental disorders, as well as people who have been victims of rape, torture, and other forms of physical, mental, or sexual abuse. Any person, due to certain circumstances, deficiencies, or dysfunctions, might be unable to fully exercise their rights.